We are all birds of Uganda - Zayyan, Hafsa (#Merky Books, 2021)
"1960s UGANDA. Hasan is struggling to run his family business following the sudden death of his wife. Just as he begins to see a way forward, a new regime seizes power, and a wave of rising prejudice threatens to sweep away everything he has built. Present-day LONDON. Sameer, a young high-flying lawyer, senses an emptiness in what he thought was the life of his dreams. Called back to his family home by an unexpected tragedy, Sameer begins to find the missing pieces of himself not in his future plans, but in a past he never knew."--Publisher.